Inland : poems - Alexander, Pamela, 1948- (Iowa poetry prize., 1997)
Pamela Alexander's poetry is characterized by inventive language, scrupulous accuracy of imagery, and a winning fusion of the comic and the deeply serious. Her subjects vary as widely as her settings, which range from the New Hampshire woods to the Arizona desert. A family life eccentric to the point of chaos, close observations of wildlife, and coastal sailing are among the poet's topics.